2007
DOI: 10.1007/s11664-007-0187-4
|View full text |Cite
|
Sign up to set email alerts
|

Silver Particle Carbon-Matrix Composites as Thick Films for Electrical Applications

Abstract: Silver particle (3 lm) carbon-matrix composites in the form of thick films (around 100 lm thick) on alumina, as prepared from pastes comprising silver and mesophase pitch particles (14 lm), have been attained. The films on alumina were fired at 650°C in nitrogen to convert pitch to carbon. The volume electrical resistivity attained ranged from 10 -5 X cm to 10 4 X cm, depending on the silver volume fraction. The percolation threshold was 12 vol% silver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previously, Hsu et al had reported a sheet resistance of 890 KΩ □ −1 for a thick film (~150 μm) of a composite of silver particles in a carbon matrix pasted over an alumina substrate. 43 The silver particles were present in the composite with ~8% volume fraction. 43 Coating of carbon black and polyelectrolytes on a nonconducting polyIJethylene terephthalate) substrate in a layer-by-layer manner was reported to have a sheet resistance of 10s of KΩ □ −1 for the film thickness of ~1.5 μm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Hsu et al had reported a sheet resistance of 890 KΩ □ −1 for a thick film (~150 μm) of a composite of silver particles in a carbon matrix pasted over an alumina substrate. 43 The silver particles were present in the composite with ~8% volume fraction. 43 Coating of carbon black and polyelectrolytes on a nonconducting polyIJethylene terephthalate) substrate in a layer-by-layer manner was reported to have a sheet resistance of 10s of KΩ □ −1 for the film thickness of ~1.5 μm.…”
Section: Resultsmentioning
confidence: 99%
“…43 The silver particles were present in the composite with ~8% volume fraction. 43 Coating of carbon black and polyelectrolytes on a nonconducting polyIJethylene terephthalate) substrate in a layer-by-layer manner was reported to have a sheet resistance of 10s of KΩ □ −1 for the film thickness of ~1.5 μm. 44 The simple microwave-based coating process of OLCSs reported here is effective in producing conducting carbon thin films.…”
Section: Resultsmentioning
confidence: 99%
“…When the ratio Ag:Fe 3 O 4 is 1.75:1 the conductivity increases about 6 orders of magnitude and then it remains approximately constant with an increase in the silver content. Even though the maximum conductivity obtained (about 10 -2 S/cm) is much lower than the conductivity of bulk silver (about 10 4 S/cm) [21], the materials with Ag:Fe 3 O 4 ratio ¥ 1.75 have acceptable values of electrical conductivity. This increase in the electrical conductivity with the silver content was also observed by Sun et al [12], who attributes this behavior to the covering of Fe 3 O 4 nanoparticles by a thin layer of metallic silver.…”
Section: Fig 3 Herementioning
confidence: 74%
“…10 6 S/m) of silver bulk. 18 This may be caused by the different size at which the Ag nanoparticles were measured. Furthermore, the conductivity of the Fe 3 O 4 /Ag core-shell nanoparticles prepared for various reaction times is also compared in Table I, showing that the conductivity of Fe 3 O 4 /Ag coreshell nanoparticles increases with the reaction time.…”
Section: Resultsmentioning
confidence: 99%